OPTIMALISASI PROGRAM TERAPI LATIHAN LOW IMPACT DENGAN DOSIS INTERMITTEN PADA WANITA MENOPAUSE DI RS EFARINA PEMATANGSIANTAR - Muliati, Muliati; Marolop Parlindungan Napitu; Isa Harpika Br. Ginting; Imelda Putri Arianti (Nusantara Hasana Journal, 2022)
Menopausal women experience various physiological changes that can reduce their quality of life, such as decreased bone density, metabolic disorders, and musculoskeletal complaints. Low-impact intermittent exercise therapy is an effective and safe non-pharmacological approach. This community service activity aims to optimize the understanding and implementation of this exercise program among menopausal women at Efarina Hospital in Pematangsiantar. The methods used included education, exercise demonstrations, and practical guidance. The results showed an increase in participants' knowledge and ability to perform the exercises independently. This program is expected to continuously improve the quality of life and physical fitness of menopausal women.